2014
DOI: 10.3310/hsdr02280
|View full text |Cite
|
Sign up to set email alerts
|

The use of a collaborative structured methodology for the development of a multifaceted intervention programme for the management of asthma (the MIA project), tailored to the needs of children and families of South Asian origin: a community-based, participatory study

Abstract: BackgroundAsthma is one of the most common chronic childhood illnesses in the UK. South Asian children are more likely to suffer from their asthma and be admitted to hospital. While this inequality needs to be addressed, standard behaviour-change interventions are known to be less successful in minority ethnic groups. Evidence suggests a need to enhance services provided to ethnic minority communities by developing culturally sensitive tailored interventions.ObjectivesThe Management and Interventions for Asthm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 119 publications
1
49
0
Order By: Relevance
“…[ 32 ] The methodological approach taken to recruit participants followed recognised approaches for working with minority ethnic communities in the UK. [ 33 , 34 ]…”
Section: Methodsmentioning
confidence: 99%
“…[ 32 ] The methodological approach taken to recruit participants followed recognised approaches for working with minority ethnic communities in the UK. [ 33 , 34 ]…”
Section: Methodsmentioning
confidence: 99%
“…Communication with the people and building relationships is stated to be foundational in research among minority communities. Recommended strategies include building trust, increasing visibility of the investigators, involving community advisors, sharing insights with the target group, and forming social networks within the community [ 13 17 ]. Recruiting minority participants can be done in various ways, including door-to-door enumeration, community approaches such as community events, and snowball methods [ 3 , 18 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge may be inconsistent given the invalid and/or inconsistent messages available on the Internet (eg milk as a source of vitamin D), conflicting public health campaigns (eg CANCERactive Safe Sun campaigns), and limited access to evidence‐based advice from health professionals. Other work on asthma in South Asians has shown that health professionals often focus on medicinal rather than behavioural approaches to self‐management and that culturally appropriate educational interventions are effective for long‐term improved health outcomes . More recent evidence suggests that it is feasible to deliver a community‐based intervention to optimize vitamin D knowledge and medication adherence in South Asians and that it is important to develop a culturally appropriate educational package …”
Section: Discussionmentioning
confidence: 99%